PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT GUANLONG PANCKINGS INDONESIA - Lisa Sulistiyowati; Dedi Mulyadi; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study looks at how work motivation influences the performance of PT Guanlong Packings Indonesia workers. This research was conducted by distributing questionnaires to company employees. Research shows that work motivation has a significant influence on how well workers perform. The main objective of this research is to understand how employee performance and work motivation relate to each other. Another goal is to identify the elements that influence this relationship